2020
DOI: 10.3390/ijerph17030706
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Seasonal Food Insecurity among Small-Scale Subsistence Farming Households in Rural Honduras

Abstract: In the context of climate change, a nutritional transition, and increased pressures to migrate internally and internationally, this study examined the relationship between seasonal food insecurity and demographic, socioeconomic, and agricultural production factors among small-scale subsistence farmers in rural northern Honduras. Anchored by a partnership with the Fundación para la Investigación Participativa con Agricultores de Honduras (FIPAH) and the Yorito Municipal Health Centre, a cross-sectional househol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 33 publications
(72 reference statements)
1
20
0
Order By: Relevance
“…Furthermore, the results pointed out here corroborate with studies that reported less food availability among families with food insecurity or socioeconomic vulnerability when compared to families with food security and higher income [34,35]. However, unlike this study, Martins and Monteiro observed greater expenditure on food and greater availability of fresh food and culinary ingredients, in households benefited by the Government Bolsa Família Welfare Program, when compared to non-beneficiaries [36].…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, the results pointed out here corroborate with studies that reported less food availability among families with food insecurity or socioeconomic vulnerability when compared to families with food security and higher income [34,35]. However, unlike this study, Martins and Monteiro observed greater expenditure on food and greater availability of fresh food and culinary ingredients, in households benefited by the Government Bolsa Família Welfare Program, when compared to non-beneficiaries [36].…”
Section: Discussionsupporting
confidence: 88%
“…Several factors such as food crops, household size, crops contribution to household food basket and crop raiding animals can be linked to household food insecurity of subsistence farmers (Nyirenda et al, 2018;Dodd et al, 2020). In Eastern Zambia, Nyirenda et al (2018) showed how crop raiding elephants of Lupande Game Management Area affected the food security of the neighboring subsistence farmers.…”
Section: Discussionmentioning
confidence: 99%
“…In Eastern Zambia, Nyirenda et al (2018) showed how crop raiding elephants of Lupande Game Management Area affected the food security of the neighboring subsistence farmers. In Hungary, Dodd et al (2020) reported larger households that do not grow maize and beans to be more likely to experience insufficient food.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations